Implementation of the Critical Thinking Blended Apprenticeship Curricula and Findings per Discipline: Foreign Language Teaching - Ovidiu Ivancu; Roma Kriaučiūnienė; Svetozar Poštič (MDPI AG, 2023)
Critical thinking is a central element in higher education, designed to respond to authentic challenges that our society currently faces: the emergence and spread of fake news, disinformation, and manipulation. There is a consensus regarding CT's importance and role in higher education. Nevertheless, CT skills are often implicitly mentioned and only occasionally included in university curricula explicitly. The present paper aims at analysing how CT can be measured and tested in higher education, and it proposes specific tasks designed to increase the use of CT within the theoretical framework defined by Peter Facione and Paul Elder. Updated course descriptions were tested, and students' feedback was analysed and discussed. CT was measured by pre-questionnaires, mid-questionnaires, and post-questionnaires to establish the effectiveness of coherently implementing CT into the course descriptions. The survey includes answers to open questions to determine the suitability of the tasks proposed. The present research is part of the international Erasmus project "Critical Thinking for Successful Jobs".